Does she deserve it? The influence of gender and meritocracy in reactions to affirmative action legislation - Silva, V.; Santos, M. H.; Rosa, M. (Social Sciences, 2021)
Gender equality is a matter for debate worldwide. In 2018, Portugal enacted legislation (Decree Law no. 62/2017) to balance gender representation on the executive boards of listed and public sector organizations with measures similar to those causing controversies in other countries. Thus, in accordance with previous research, a study took place to examine the attitudes towards the justice of this legislation and the role of merit in these attitudes. This study (n = 129 women and 94 men) deployed an experimentally manipulative type of affirmative action program to consider the role of individual perceptions of the justice of the legislation coupled with the influence of beliefs in meritocracy and participant gender. The results identify how the type of affirmative action impacted on the perceived justice, also influenced by merit, which seems normative and fundamental to evaluating the justice of such legally stipulated provisions. Nonetheless, objectively evaluating candidate merits revealed difficulties in disentangling this process from personality traits.